Experimental Study on the Influence of Moisture Content during Gas Depressurization Extraction - Yuexia Chen; Xuexi Chen; Jiang Xu; Tingxiang Chu (Advances in Materials Science and Engineering)
Although there are many reports about the influence of moisture in the process of gas extraction, studies about the influence of moisture on gas flow, permeability, and coal deformation by experimental system analysis are lacking. Physical simulations of gas depressurization extraction using triaxial servo-controlled seepage equipment for hot-fluid-solid coupling were conducted. The gas flow rate, permeability, and strain were analysed during gas depressurization extraction. The relationship between gas flow rate and gas pressure was a quadratic polynomial. Permeability and strain changed continuously with the decrease of gas pressure and interacted with each other during gas depressurization extraction. In the initial stage, the effective permeability decreased. With the continuous decrease of gas pressure, the permeability gradually recovered. When the gas pressure dropped to about 0.6 MPa, the permeability increased rapidly and the corresponding volumetric strain increased gradually. With the increase of moisture content, the relationship between gas flow rate and gas pressure became less significant. The experiments showed that the higher the moisture content, the lower the effective permeability and the larger the volumetric strain.